PERAN HUKUM PIDANA INTERNASIONAL DALAM MENGATASI GENOSIDA PADA KONFLIK ISRAEL-PALESTINA - Rindang Gici Oktavianti (HUKMY : Jurnal Hukum, 2025)
ABSTRACT In overcoming the genocide that occurred in the Israeli-Palestinian conflict, international criminal law is greatly assisted, especially through court mechanisms such as the International Criminal Court (ICC). The purpose of this law enforcement is to prosecute those who commit serious crimes, provide justice to victims, and encourage accountability at the international level. This normative legal research uses a statutory regulatory approach. The legal materials used in this study are primary legal materials, secondary legal materials, and tertiary legal materials. The author uses a literature study as a search method, and the method of analyzing legal materials used for this writing is qualitative. International criminal law, through instruments such as the Rome Statute and the role of the International Criminal Court (ICC), serves as a mechanism to respond to and prosecute international crimes, including genocide. Although the ICC has jurisdiction to investigate and prosecute violations that occur, various political and legal factors often hinder the process. This study highlights the importance of accountability and justice for victims, as well as the need for international cooperation to ensure that serious violations are not left unpunished. Thus, international criminal law can contribute to conflict resolution and the restoration of trust between the parties involved.